Systematic approaches to a successful literature review - Booth, Andrew; Papaioannou, Diana; Sutton, Anthea (Los Angeles ; Thousand Oaks, Calif. : Sage, 2012)
"Reviewing the literature is an essential part of every research project. This book takes you step-by-step through the process of approaching your literature review systematically, applying systematic principles to a wide range of literature review types. Through numerous examples, case studies and exercises, the book covers often neglected areas of literature review such as concept analysis, scoping and mapping"--Jacket.
Keywords: Research; Research; Review Literature as Topic